Design and Simulation of MEMS Force Sensor for Detection of Human Inhale and Exhale Rate - G.R.K. Prasad,L. Sreeharsha, D Arthi, M.Siva Kumar,P.Sivakrishna, C. Venkataramanan, A.Manikandan (Design Engineering, 2021)
Medical care assumes a significant function in enhancing an individual's standard of health. Persistent watching of the medical conditions is required particularly in the infirmary to observe out for one's prosperous condition. Observing a patient in dispensary and ambulances is an imperative assignment that includes part of human intercession and cannot be dependable constantly. Henceforth, a need is felt to motorize different checking exercises. In this proposed design model, a diaphragm(400 μm x 400 μm), substrate (530 μm x 510 μm), and thickness (10 μm)been designed to screen the Highest sensitivity semiconductors by estimating displacement sensitivity based upon the force inhale or exhale rates of person using Hooke’s law (Stress = K x Strain) and at different inputs of Eigen-frequency (For, Ge 2.406 MHz at 0.0752 displacement, for 10 N force on diaphragm) and capacitance sensitivity depending upon the input voltage. This system support in the planning of aMiniature Electro-Mechanical Systems based high sensitivity pressure sensor for better valuation and diagnosis of patient.